Efficacy of Ceftiofur and Marbofloxacin in the treatment of staphylococcal endometritis in cross-bred cows - SENGUPTA, D; KUMAR, DEEPAK; AZAD, C S; SHEETAL, S K; KUMARI, SAVITA; KUMAR, SANJAY; KUMAR, KESHAV (The Indian Journal of Animal Sciences, 2024)
Endometritis and sub-clinical endometritis are considered important factors for conception failure and repeat breeding conditions. Intra-uterine antibiotics infusion is generally recommended as the choice of treatment for endometritis. This work was performed to test the efficacy of ceftiofur sodium and marbofloxacin in the treatment of endometritis in cross-bred cows caused by Staphylococcus sp. One hundred cows found positive for Staphylococcus sp. from culture of uterine contents were grouped into two groups (CEF and MARB) of fifty cows each. Group CEF was treated with 1 g ceftiofur sodium (Xceft®, Alembic, India) intra-muscularly (IM) for five days and Group MARB was treated with 10% marbofloxacin (Marbomet®, Intas, India) at the dose rate of 2 mg/kg body weight IM once daily for 5 days. Animal from MARB and CEF groups were inseminated on next observed estrus after treatment and the conception rate was 52% and 32% compared to 60% in healthy control group, the difference being highly significant. The study reported antibiotic marbofloxacin as better alternative choice for the treatment of endometritis caused by Staphylococcus sp. in cross-bred cows.